The Ketema Ra’isi site near the Tekkeze river in Tigray (Ethiopia): A possible Aksumite site in the context of Ezana’s war against the Nobā - Michela Gaudiello (Polish Archaeology in the Mediterranean, 2021)
The ruins of the Ketema Ra’isi sites in the Ethiopian northern Tigray could prove to be the southwesternmost site of the Aksumite empire at least during the times of king Ezana. The mound of ruins contains a residential complex inside an enclosure wall showing typical Aksumite architectural building techniques. Three Aksumite coins collected from the site yield a terminus ante quem date for settlement in the Middle Aksumite period (mid-4th century AD). Therefore, the potential of the site for future archaeological exploration by the PolART expedition is substantial.